Care as dissent in the art of Georgina Maxim, Gladys Kalichini, Kresiah Mukwazhi, Masimba Hwati and Léonard Pongo - Muchemwa, Fadzai Veronica (Rhodes University, Faculty of Humanities, Department of Fine Art)
The concept of care is proposed as an ethical and practical framework for the reading of the artistic and writing practices of Georgina Maxim, Kresiah Mukwazhi, Gladys Kalichini, Léonard Pongo and Masimba Hwati. In their practices, dissent is both an existential crisis and a constitutive practice. Through small actions, they offer up new narratives. The notion of seeing care as a form of dissent is to simply reflect on the artistic practices that are integrated with or responsive to forms of political protest and dissent based on ethical care practices and what it means to align with those things that matter to us and distancing ourselves from those things that do not. The thesis explores the ethic of care, its possibilities as a dissenting approach, and provides a narrative description of five case studies that exhibit different expressions of care in contemporary art. By prioritising care, there is an educational interest in creating resources and themes for a politically engaged approach to artistic practice and the creation of art. This study also aims to shed light on the power of art as a tool for social and political commentary, and the role of artists as agents of change in society. The study focuses on how these artists use their art to challenge societal norms and political structures, embodying the concept of care as a form of resistance. It underscores the importance of understanding the context in which art is created and the messages it conveys, particularly in societies where freedom of expression may be constrained. The study further investigates how these elements are presented in different ways to show the different manifestations of care and dissent. Through semi-structured interviews, analysis of relevant texts, and a detailed visual analysis of selected works from the five artists, the situational approach was used to explore how meanings are negotiated. The outcome is an expanded proposal for care as dissent and a listening guide as a tool or approach in helping us to listen to marginalised voices, validate experiences, identify barriers and building empathy.
Keywords: Dissenting opinions; Ethics of care; Disruption; Art -- Political aspects -- Africa; Recognition; Art and society